Aminoglycoside detection using a universal ELISA binding procedure onto polystyrene microtiter plates in comparison with HPLC analysis and microbiological agar-diffusion assay - Sachetelli, Sébastien; Beaulac, Christian; Lagacé, Jacqueline (Biochimica et biophysica acta, 1998)
The use of enzyme-linked immunosorbent assay for the detection of aminoglycosides has been hindered due to low molecular weight compound adsorption to solid phases. Here, we describe an enzyme-linked immunosorbent assay based on the treatment of polystyrene microtiter plates with Alcian blue prepared in acetic acid prior to coating with the antibiotic. Whereas no detection of tobramycin was possible on commercially treated or untreated enzyme-linked immunosorbent assay plates, the Alcian blue treatment permitted detection of 0.025 and 0.05 μg ml −1 of tobramycin respectively using 0.05 and 0.1% of Alcian blue with a coefficient of variation of 1.85 and 7.69%, respectively. Comparative studies of five tobramycin samples of unknown quantity using enzyme-linked immunosorbent assay and high-performance liquid chromatography gave equivalent results while those done via microbiological agar-diffusion assay were an overestimation of the actual quantity. The use of the Alcian blue pretreatment enzyme-linked immunosorbent assay procedure has permitted, in previous studies, the measure of antibodies against synthetic peptides and phospholipids. Subsequently, our demonstration of the sensitivity and reliability of this method in the quantification of tobramycin strongly suggests that the use of Alcian blue pretreatment in enzyme-linked immunosorbent assay can be applied universally to avert molecule immobilization problems on solid phases.